Communication in nursing - Balzer-Riley, Julia W. (Elsevier/Mosby, 2012)
Beyond the basic concepts of therapeutic communication, Communication in Nursing, Seventh Edition is a unique approach to interacting with your patients and colleagues with empathy and sensitivity. This practical resource addresses a wide array of topics, including being assertive, electronic communication, respect, humor, confrontation, and requesting support, with a personal touch conveyed through quotes, stories, and poetry